Enhanced transmission of malaria parasites to mosquitoes in a murine model of type 2 diabetes. (December 2016) - Pakpour, Nazzy; Cheung, Kong; Luckhart, Shirley
Abstract Background More than half of the world's population is at risk of malaria and simultaneously, many malaria-endemic regions are facing dramatic increases in the prevalence of type 2 diabetes. Studies in murine malaria models have examined the impact of malaria infection on type 2 diabetes pathology, it remains unclear how this chronic metabolic disorder impacts the transmission of malaria. In this report, the ability type 2 diabetic rodents infected with malaria to transmit parasites toAnopheles stephensi mosquitoes is quantified. Methods The infection prevalence and intensity ofAn. stephensi mosquitoes that fed upon control or type 2 diabetic C57BL/6 db/db mice infected with either lethalPlasmodium berghei NK65 or non-lethalPlasmodium yoelii 17XNL murine malaria strains were determined. Daily parasitaemias were also recorded. Results A higher percentage of mosquitoes (87.5 vs 61.5 % forP. yoelii and 76.9 vs 50 % forP. berghei ) became infected following blood feeding onPlasmodium -infected type 2 diabetic mice compared to mosquitoes that fed on infected control animals, despite no significant differences in circulating gametocyte levels. Conclusions These results suggest that type 2 diabetic mice infected with malaria are more efficient at infecting mosquitoes, raising the question of whether a similar synergy exists in humans.